Early selection and classification of yerba mate progenies - Wendling, Ivar; Sturion, José Alfredo; Stuepp, Carlos André; Fioravante Reis, Cristiane Aparecida; Ramalho, Magno Antonio Patto; Resende, Marcos Deon Vilela de (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate the feasibility of early selection of open-pollinated yerba mate (Ilex paraguariensis) progenies, and to classify the best parents and candidates for clones. The germplasm is composed of 140 progenies collected from areas within the natural distribution of the species in Southern Brazil and a commercial genotype (control). The experiment was established in Ivaí, in the state of Paraná, Brazil, in March 1997, in randomized complete blocks, with ten replicates, and linear plots of six plants. The commercial mass (kg per plant) of leaves and branches smaller than 7 mm was harvested at 2.5, 4.5, 6.5, and 18.7 years of age. The statistical evaluation was performed using the mixed model procedure with restricted maximum likelihood/best linear unbiased prediction, using the Selegen software. High selective accuracy, significant progeny effects, and genetic variability for commercial mass production were observed for the four harvesting ages. The application of early selection for leaf mass production is feasible for yerba mate progenies harvested at 6.5 years. The selection of the best trees, either for use as parents or as candidates for cloning, provides significant gains for the genetic breeding of yerba mate.